Diversity and distribution of plankton community and physico-chemical parameters in wishpond, wishpond-aquaponics system and traditional fish pond (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
This study was designed to determine the interrelationship between physico-chemical parameters and plankton community in three different aquaculture systems (wishpond, wishpond aquaponics and traditional fish pond). The water quality parameters, dissolve oxygen (DO), temperature, pH, ammonia, alkalinity and transparency were monitored and found within the recommended range. Different phytoplankton of four (4) different groups were observed where Chlorophyceae group was the most dominant (8.03±0.19) × 103 cells/l in wishpond system and Euglenophyceae was the less dominant (45.86±1.15) × 103 cells/l in traditional pond system. In addition, Zooplankton of Rotifera was found the most dominant (17.81±0.09) × 103 cells/l with following Cladocera and Copepoda. A significance difference were observed in case of plankton groups among three different aquaculture systems. The interrelationship among the physico-chemical parameters, temperature showed strongest relationship with all the other physico-chemical parameters where transparency showed no relation with dissolve oxygen. In case of phytoplankton groups, all four groups showed more or less positive relationship in all three different aquaculture system. The findings of this study will assist small-scale producers in choosing and properly operating a simple aquaponics system.Asian Australas. J. Biosci. Biotechnol. 2022, 7 (1), 13-22